The article defines the essence of the concept "student family". The main factors of youth readiness to create a family are highlighted. The specific problems faced by student families are characterized, the main psychological causes of conflicts in stude - Posvistak, O.; Efimenko, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article defines the essence of the concept "student family". The main factors of youth readiness to create a family are highlighted. The specific problems faced by student families are characterized, the main psychological causes of conflicts in student families are identified and ways to solve social and psychological problems of the family are analyzed. The benefits of student families are shown.
Keywords: family psychology, young family, student family, family conflict